Nursing ethics in a developing country - Annatjie Botes (AOSIS, 1999)
Nursing is a true profession, distinguished by its philosophy of care, its full-time commitment to human well being, its particular blend of knowledge and skills and its valuable service to the community (Curtin & Flaherty, 1982:92). Ethics is vital to nursing. Being a professional implies ethical behaviour and knowledge of what it means to be ethical (Pera & Van Tonder, 1996:v). Ethics is the foundation of committed service to humankind. When nurses practice in an ethical manner they should adhere to ethical principles like autonomy, beneficence, justice, veracity, fidelity, confidentiality and privacy.